Validating a new oscillometric device for aortic pulse wave velocity measurements in children and adolescents - Thurn-Valsassina, Daniela; Shroff, Rukshana; Baig, Sabrina; Doyon, Anke; Jacobi, Christoph; Zeller, Rene; Querfeld, Uwe; Schaefer, Franz; Wühl, Elke; Schmidt, Bernhard M.W.; Melk, Anette (American journal of hypertension, 2011)
Pulse wave velocity (PWV) is an indicator of aortic stiffness and a predictor of cardiovascular risk. Applanation tonometry (e.g., SphygmoCor) is a well-established method to measure aortic PWV (aPWV). The Vicorder, a new oscillometric device, has not been validated in children and adolescents.We performed intra- and interobserver repeatability studies in 14 individuals using the Vicorder. Vicorder and SphygmoCor measurements were compared in 156 healthy children (6-18 years) using two different path length measurements.Intra- and interobserver repeatabilities of the Vicorder were excellent with coefficients of variation of 5.6% and 5.8% and intraclass correlation coefficients (ICCs) of 0.8 and 1.0. aPWV calculated using the distances (suprasternal notch-to-femoral recording point) - (suprasternal notch-to-carotid artery), the path length most commonly used in adults, revealed a mean of 4.8 ± 0.7 m/s for SphygmoCor and 4.9 ± 0.6 m/s for Vicorder. The percentage deviation between both devices was 13.0% and the limit of agreement (LoA) ranged from −1.0 to 1.7 m/s reflecting a good concordance. Using a path length that measured the distance from suprasternal notch to femoral recording point via the umbilicus (Umb), an even better agreement was found (percentage deviation: 11.8%, LoA: −1.0 to 1.6 m/s).Vicorder aPWV values are similar to those obtained by SphygmoCor applanation tonometry. The best agreement between devices was obtained with the path length that most accurately describes the aortic tree. Excellent intra- and interobserver repeatability and ease of measurements make Vicorder appropriate for large multicentre studies in children and adolescents.American Journal of Hypertension, advance online publication 25 August 2011; doi:10.1038/ajh.2011.147